2011
DOI: 10.1002/mrd.21377
|View full text |Cite
|
Sign up to set email alerts
|

Mouse versus rat: Profound differences in meiotic regulation at the level of the isolated oocyte

Abstract: Cumulus cell-enclosed oocytes (CEO), denuded oocytes (DO) or dissected follicles were obtained 44–48 h after priming immature mice (20–23-days-old) with 5 IU or immature rats (25–27-days-old) with 12.5 IU of equine chorionic gonadotropin, and exposed to a variety of culture conditions. Mouse oocytes were more effectively maintained in meiotic arrest by hypoxanthine, dbcAMP, IBMX, milrinone, and 8-Br-cGMP. The guanylate cyclase activator, atrial natriuretic peptide, suppressed maturation in CEO from both specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 64 publications
0
14
1
Order By: Relevance
“…Feline oocytes also appeared to be highly sensitive to IBMX since 100 mM maintained the majority of oocytes at the GV stage, similar to observations in murine oocytes (Downs et al 1988;Downs 2011). This is in contrast to studies of bovine and porcine oocytes, in which much higher concentrations of IBMX (500 to 5000 mM) had less pronounced effects on meiosis (Bilodeau et al 1993;Fan et al 2002;Laforest et al 2005).…”
Section: Reversible Meiotic Arrest In Feline Oocytescontrasting
confidence: 51%
See 2 more Smart Citations
“…Feline oocytes also appeared to be highly sensitive to IBMX since 100 mM maintained the majority of oocytes at the GV stage, similar to observations in murine oocytes (Downs et al 1988;Downs 2011). This is in contrast to studies of bovine and porcine oocytes, in which much higher concentrations of IBMX (500 to 5000 mM) had less pronounced effects on meiosis (Bilodeau et al 1993;Fan et al 2002;Laforest et al 2005).…”
Section: Reversible Meiotic Arrest In Feline Oocytescontrasting
confidence: 51%
“…Other studies have reported 0 (Godard et al 2009) to 21% (Luvoni et al 2006) of feline oocytes undergoing spontaneous maturation and reaching MII, suggesting that other factors influence spontaneous maturation aside from the presence of gonadotrophins or growth factors. For example, the amount and type of metabolic substrates available in the culture medium influence the rate of spontaneous maturation in rodents and cattle in a species-specific manner (Bilodeau-Goeseels 2006;Downs 2011). In addition, intact COCs can consume a large amount of carbohydrates during in vitro maturation (Sutton-McDowall et al 2004;Herrick et al 2006b;Stokes et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of the cGMP isozyme, 8-Br-cGMP, needed in our experiments to completely inhibit PDE3A activity was much higher and non-physiologic, this is most likely due to the imidizole ring substitution, required to make the compound soluble and membrane permeable; this increases the IC 50 65-fold compared to unmodified cGMP (38). Although a higher dose is required to exert a similar effect as native cGMP, 8-Br-cGMP is widely used in oocyte meiosis studies and is a suitable model agent for in vitro experiments (39, 40). …”
Section: Discussionmentioning
confidence: 99%
“…This action may be unique in the mouse, because it is the only species thus far tested where oocyte maturation is under positive control by AMPK. Indeed, stimulation of AMPK in cow, porcine and rat oocytes does not trigger meiotic resumption (Bilodeau-Goeseels et al 2007;Mayes et al 2007;Tosca et al 2007;Downs 2011).…”
Section: Maintenance Of Meiotic Arrestmentioning
confidence: 99%